Hepatitis C virus genotyping methods: Evaluation of amplisens® HCV-1/2/3-FRT compared to sequencing method - Mohamed N.A.; Rashid Z.Z.; Wong K.K. (Wiley-Liss Inc., 2024)
Background: Hepatitis C virus (HCV) genotyping is important for treatment and epidemiological purposes. The objective of this study was to evaluate the performance of AmpliSens® HCV-1/2/3-FRT kit in comparison to sequencing method for genotyping. Methods: A total of 17 samples collected from December 2009 to January 2011 were analyzed. Reverse transcriptase polymerase chain reaction (PCR) was performed, followed by sequencing technique. Results were analyzed based on sequence information in GenBank. A second genotyping method (AmpliSens® HCV-1/2/3-FRT) was done, which differentiates HCV genotypes by means of real-time hybridization-fluorescence detection. Results: From 17 samples, four were untypeable by AmpliSens® HCV-1/2/3-FRT. Eleven of 13 (84.6%) results showed concordant genotypes. A specimen that was determined as genotype 3a by sequencing was genotype 1 by the AmpliSens® HCV-1/2/3-FRT. Another specimen that was genotype 1 by sequencing was identified as genotype 3 by AmpliSens® HCV-1/2/3-FRT. Conclusion: HCV genotyping with AmpliSens® HCV-1/2/3-FRT using real-time PCR method provides a much simpler and more feasible workflow with shorter time compared to sequencing method. There was good concordance compared to sequencing method. However, more evaluation studies would be required to show statistical significance, and to troubleshoot discordant results. AmpliSens® HCV-1/2/3-FRT does differentiate between genotype but not until subtype level.